1975
DOI: 10.1002/macp.1975.021761020
|View full text |Cite
|
Sign up to set email alerts
|

Zur stereospezifischen Polymerisation von Methylmethacrylat mit Grignard‐Reagens

Abstract: ZUSAMMENFASSUNG:Gegenstand unserer Untersuchungen war die Konfiguration von Polymethylmethacrylat (PMMA), das aus Methylmethacrylat mit Butylmagnesiumchlorid in Toluol bei -50 "C einmal in Abwesenheit (Blank-Polymerisation) und einmal in Gegenwart von vorgelegtem isotaktischern PMMA (Replica-Polymerisation) dargestellt wurde.Es zeigte sich, da8 bei der Blank-Polymerisation eine Beziehung besteht zwischen dem Monomer-Umsatz und der Konfiguration der erhaltenen Polymerisate: die bei niedrigen Umsatzen ( < 10%) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[14][15][16][17][18][19][20][21][22][23] For instance, the polymerization of acrylic acid is influenced by the presence of poly(N-vinylpyrrolidone) as the template. [24][25][26] Dilatometry and conductimetry were used to investigate the kinetics of the reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22][23] For instance, the polymerization of acrylic acid is influenced by the presence of poly(N-vinylpyrrolidone) as the template. [24][25][26] Dilatometry and conductimetry were used to investigate the kinetics of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of a template macromolecule on the polymerisation of monomers which can interact with it by means of hydrogen bondings has been widely investigated in the past by several authors. [14][15][16][17][18][19][20][21][22][23] For instance, the polymerization of acrylic acid is influenced by the presence of poly(N-vinylpyrrolidone) as the template. [24][25][26] Dilatometry and conductimetry were used to investigate the kinetics of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The time required to attain the adsorption equilibrium was determined according to our 200 Cl Cl E preliminary result obtained for stactic PMMA. 11 The rate of adsorption from its chloroform solution onto silica gel was very fast, and an adsorption equilibrium appeared to be attained after a time ranging from 0.5 to 2 hr. However, prolonging the time of observation, we found that this equilibrium was merely apparent and the polymer amount adsorbed at this stage began to decrease very slowly; the true equibrium was finally attained after about 20 hr.…”
Section: Adsorption Isothermsmentioning
confidence: 99%